(untitled) (Bangladesh Journal of Agricultural Research, 2012)
The yield gap and the production constraints in the rice-wheat (R-W) system in eastern Uttar Pradesh were studied. The yield gap II (difference between the yield obtained at nearest demonstration plot and actual yield obtained on farmers’ fields in a particular region) has been found 45 percent and 38 percent in rice and wheat crops, respectively, in the irrigated rice-wheat system. The technological and socio-economic constraints have accounted for 54 percent and 46 percent of the yield gap, respectively, in the system. Soil-related constraints rank first, followed by weed-related constraints. Among the individual constraints, zinc deficiency rank first followed by nitrogen deficiency and incidence of Phalaris minor. The study has concluded that for the sustainability of the R-W system, priority should be accorded to bridge the existing yield gap through addressing the production constraints. DOI: http://dx.doi.org/10.3329/bjar.v36i4.11749 Bangladesh J. Agril. Res. 36(4): 623-632, December 2011